Functional equations for homogeneous polynomials arising from multilinear mappings and their stability - Schwaiger, Jens (Annales Mathematicae Silesianae, 1994)
Some characterizations of homogeneous polynomials and of polynomials in general are given. This is done not only in the usual case but also for vector spaces over non archimedean valued fields. Moreover stability results in connection with these characterizations are given.